USE OF FINANCIAL INSTRUMENTS AT VARIOUS LIFE STAGES OF COMPANIES - V. Zaitsev (Вестник Северо-Кавказского федерального университета, 2022)
This work is devoted to the study of the life cycles of organizations and the analysis of financial instruments that are most suitable for certain life cycles. The problem of choosing the most optimal source of financing is relevant, since many companies often make mistakes when choosing financial instruments. To solve this problem, there are various theories and models of life cycles. At various stages of the life cycle, companies, including oil and gas companies, have access to more and more new fnancial instruments. As a rule, the basis for fnancing is a thorough analysis of the project or company and the factors affecting their well-being. There are various theories of the life cycles of organizations, in this work we will consider some of them and offer our own theory of defning the life cycle. Taking into account the peculiarities of life cycles, we present the optimal sources of fnancing. In the study, we will consider the existing life cycles of companies that are identifed by the scientifc community and characterize them. Based on the life stages proposed by various researchers, we will choose the most optimal ones for research.